Os significados culturais em canções da banda de rock brasileiro Capital Inicial - Acosta, José Luiz da Silva (2016)
This research talks about the brazilian rock, focused on the cultural meanings that can be built in its discourse. The main point of this research is to investigate this effects in social groups as the rock, starting from the songs of this genre that were produced in brazil. Therefore, some questions were formulated for which objective, is to find a north, they are: a) How can be built the cultural meanings of the rockers group? b) How can the global or local cultural meanings be blended? c) the cultural meanings found confirm or deny the stereotype built about Rockers? The research is contained in the field of Applies Linguistics which is about the language in real conditions of use (CAVALCANTI, 1986; ALMEIDA FILHO, 1991, 2001; MOITA-LOPES, 1998, 2006), caracterized by his qualitative and interpretative nature which the concern is not stablish universal verity, but study specific situations (DENZIN e LINCOLN, 20006; BORTONI-RICARDO, 2009). The theoritical foundation for the development of this apply came from the Antropology studies (CANCLINI, 2009, 2011), from the Cultural Study's camp (BHABHA, 1998; HALL, 2000) and the Feminist Studies (BUTLER, 1988, 1994, 2003). Are included in this paper the songs of the band Capital Inicial Veraneio Vascaína , 1886; Cai a noite . 1991; Quatro vezes você , 2002; and Coracao vazio , 2004. These sources come from especific music portals on internet. For making the data, the sociologic method of the language was applied, related to the bakhtinian theory (BAKHTIN/VOLOCHINOV, 1997; BAKHTIN, 1998, 2003; FIORIN, 2008; BRAIT, 2005; SILVEIRA, 2012) which the songs are taken while the discursive genres, composed by tematic theme, composicional estructure, and style, they are all submissive to a comucational area. From this research, the results found are that the cultural meanings are made up socialy, for historical process, and can be noticed for the collocutor from the point of the united elements in the text, with the informations about the prodution conditions, circulation and reception of the songs. More than that, there exists a presence of meanings related to the brazilian context of determined songs, while other do not, that clarifies a balance between the global and locals meanings. To be finished, the complexity of the person identity formation of someone prevents that can be told categoricaly that the stereotype of rockers was forced, or denyed, up the analized songs, once that some marks are linked to this groupd were found and some did not.